Índices de preço e o mercado imobiliário: Literatura e ilustraç\~ao - o caso de S\~ao Paulo - Pedro H. M. Albuquerque; Bernardo Alves Furtado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper is a theoretical review of consumer price indices, with an emphasis on the specifics of the real estate market, highlighting advantages and limitations. It discusses the following indices of average prices: Laspeyres, Paasche, Fisher and Jevons. In addition, it presents two variations of construction by hedonic methods: with insertion of dummy variables and imputation. Typical specificities of the real estate market, such as property attributes, its long temporality and urban insertion, recommend greater care when building indices for the housing market. The paper presents some recent theoretical advances for the real estate market and concludes with a brief application for Sao Paulo.
Keywords: C43; R32; E31; 330; prices indices; real estate market; Sao Paulo